EPC and 4G packet networks : driving the mobile broadband revolution - Olsson, Magnus (Academic Press, 2012)
Future mobile access networks will require upgraded telecommunications networks; 3G LTE/ SAE is the next step, allowing data rates above 100 Mbps. Telecommunications engineers will need to understand the new SAE/ EPC architecture and its tendency towards automatic configuration, but the complexity, length and dryness of the standards documents make it difficult for them to find the information they need and work out how to apply it to their daily product and network development. This book - a new edition of SAE and the Evolved Packet Core - provides clear, concise and comprehensive coverage of the entire SAE/ EPC architecture, explaining concepts and standards and how they are used in commercial service settings. More than just a precis of the standards, it gives real insight into their development and the real-world scenarios in which they have been used since the publication of the first edition. This second edition places more emphasis on key aspects such as mobile systems and protocols (Diameter, GTP, S1-AP), and includes new coverage of femtocells, SIPTO, LIPA, LTE relay and LTE Advanced. SAE is the core network that supports LTE, the next key stage in development of the UMTS network to provide mobile broadband. It aims to provide an efficient, cost-effective solution for the ever-increasing number of mobile broadband subscribersThere is no other book on the market that covers the entire SAE network architecture; this book summarizes the important parts of the standards, but goes beyond mere description and offers real insight and explanation of the technologyFully updated with the latest developments since the first edition published, and now including additional material and insights on industry trends and views regarding future potential applications of SAE.